2015
DOI: 10.1115/1.4029401
|View full text |Cite
|
Sign up to set email alerts
|

Design for Control of Wheeled Inverted Pendulum Platforms

Abstract: In this paper, we study five aspects of design for wheeled inverted pendulum (WIP) platforms with the aim of understanding the effect of design choices on the balancing performance. First, we demonstrate analytically and experimentally the effect of soft visco-elastic tires on a WIP showing that the use of soft tires enhances balancing performance. Next, we study the effect of pitch rate and wheel velocity filters on WIP performance and make suggestions for design of filters. We then describe a self-tuning lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We define y as a function of φ and θ in (32). Hence, the derivatives of y with respect to t are calculated by (33) and (34) as follows:…”
Section: B Lam Linearization Of the Nonlinear Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We define y as a function of φ and θ in (32). Hence, the derivatives of y with respect to t are calculated by (33) and (34) as follows:…”
Section: B Lam Linearization Of the Nonlinear Systemmentioning
confidence: 99%
“…The installed controllers strongly and stably maintained the robot's position at the desired point in simulations, but their performance was not tested in physical experiments. The authors [33] controlled the torque and velocity of wheeled inverted pendulum motors in an analytical simulation study, and described the trade-offs between the control methodologies in different application situations.…”
mentioning
confidence: 99%
“…For (b), Medrano-Cerda [26] considered a scheme based on velocity-sign compensation in the inverted pendulum on a cart. Also, Vasudevan et al [27] compensated friction via a passivity-based observer for the wheeled inverted pendulum. Eom and Chwa [28] compensated friction, system uncertainties, and an external disturbance through a nonlinear observer for the pendubot.…”
Section: Complexitymentioning
confidence: 99%
“…Having undertaken the literature review, it was found that the papers dealing with reduction of friction-induced limit cycles use compensation techniques that have the following disadvantages: (i) most compensation terms are complex and require the numerical values of the frictional parameters [27] and (ii) undercompensation leads to steady-state error and overcompensation may induce limit cycles [9,40]. Although an important effort has been done in [26] to reduce the limit cycle in the inverted pendulum on a cart, to the authors' knowledge, the elimination of the limit cycle in the inverted pendulum on a cart has not been achieved until now.…”
Section: Complexitymentioning
confidence: 99%
“…This aims to highlight the interactions between design and control, which are generally treated as separate domains in engineering practice. Design-for-control approaches have been proposed for specific underactuated mechanisms [16], [17] and for mechatronic systems in general [18], however they have mostly focused on the effect of individual parameters on performance. In this respect, defining design In this work, potential-energy shaping design principles, which were originally introduced for static balancing [5], and energy-shaping control [7] are combined within the same analytical formulation.…”
Section: Introductionmentioning
confidence: 99%